Virus-induced gene silencing (VIGS) in cape gooseberry (Physalis peruviana L., Solanaceae) - Jaime A. Osorio-Guarín, Francy L. García-Arias, Roxana Yockteng (Pontificia Universidad Javeriana, 2019)
Cape gooseberry (Physalis peruviana, L.) is a herbaceous plant belonging to the Solanaceae family that produces an edible berry appreciated for its nutraceutical and pharmaceutical properties. Its production is often limited by diseases and reproducible fruit quality. Recent studies have reported genes associated with fruit quality and resistance response to the root-infecting fungus Fusarium oxysporum f. sp. physali (Foph,) which causes vascular wilt. In order to standardize a method to validate the biological function of candidate genes in the non-model species P. peruviana, we tested the robust approach in reverse genetics, virus-induced gene silencing (VIGS). In this study, we validated and optimized VIGS using an insert of the phytoene desaturase (PDS) gene in a silencing viral vector generated from tobacco rattle virus (TRV). Leaves infiltrated with Agrobacterium (GV3101 strain) showed photo-bleached segments, which were distinctive for PDS suppression at 7 days post-infection (dpi). More than half of the treated plants showed photo-bleaching, indicating an efficiency rate of 50 % of the VIGS protocol. The results of this study showed that VIGS can be used for future functional gene characterization implicated in the immune response, disease resistance and fruit quality in capegooseberry.